The Implementation of Jogo Tonggo: Living Hadits in RW V Kedungwuluh Environment, West Purwokerto as A Prophetic Solution in The Middle of the Covid-19 Pandemic - Nur Wakhid (LPPM UIN Saizu Purwokerto, 2022)
Based on Circular Number 1 of 2020, the Governor of Central Java Province instructed all Regents and Mayors throughout Central Java to form the Jogo Tonggo movement. This policy aims to invite all elements of society to work together to prevent and contain the spread of Covid-19. This is in line with the prophetic solution in responding to the pandemic contained in the Prophet's hadith. Namely, solutions based on prophecy in the form of humanization (amar ma'rūf), liberation (nahī munkar), and transcendence (tu'minūna billāh). The application of these three prophetic values ​​has positive implications for the life of hadith in the midst of society. This study aims to discuss the living hadith phenomenon of the Jogo Tonggo movement in RW V, Kedungwuluh Village, West Purwokerto District, Banyumas Regency. This research is doctrinal normative using a statutory approach, a conceptual approach, and a case approach. The results showed that the Jogo Tonggo policy had been implemented well. In their daily practice, local residents have been educated to implement health protocols in a disciplined manner so that the spread of Covid-19 can be minimized.